2006
DOI: 10.1007/s10194-006-0287-1
|View full text |Cite
|
Sign up to set email alerts
|

Neurophysiological assessment of craniofacial pain

Abstract: This review deals with the diagnostic usefulness of neurophysiological testing in patients with craniofacial pain. Neurophysiological testing of trigeminal nerve function relies on trigeminal reflexes and laser-evoked potentials (LEPs). This review briefly describes the physiology of trigeminal reflexes and LEPs, reports normal values and highlights the neurophysiological abnormalities in the main clinical conditions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0
1

Year Published

2009
2009
2019
2019

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 65 publications
0
9
0
1
Order By: Relevance
“…Other advantages with laser stimulators include the possibility to emit a very brief pulse in the range from just a few ms to 200 ms, which allows the recording of time-locked electrophysiological responses like laser-evoked reflexes and brain potentials (164)(165)(166)(167)(168)(169)(170)(171)(172). Argon laser stimuli (k = 488-515 nm), CO 2 , copper vapour (k = 578 nm), neodymium-yttrium-aluminium garnet (Nd-YAG) (k = 1064 nm) and thulium-YAG (1800 nm) laser stimuli have up to now been used in the oro-facial region to test thermal sensations (172)(173)(174)(175)(176)(177). Reflection of the laser light is dependent on the wavelength, which should be taken into consideration if the thermal sensitivity of different tissue surfaces is to be compared (175).…”
Section: Thermal Stimulationmentioning
confidence: 99%
“…Other advantages with laser stimulators include the possibility to emit a very brief pulse in the range from just a few ms to 200 ms, which allows the recording of time-locked electrophysiological responses like laser-evoked reflexes and brain potentials (164)(165)(166)(167)(168)(169)(170)(171)(172). Argon laser stimuli (k = 488-515 nm), CO 2 , copper vapour (k = 578 nm), neodymium-yttrium-aluminium garnet (Nd-YAG) (k = 1064 nm) and thulium-YAG (1800 nm) laser stimuli have up to now been used in the oro-facial region to test thermal sensations (172)(173)(174)(175)(176)(177). Reflection of the laser light is dependent on the wavelength, which should be taken into consideration if the thermal sensitivity of different tissue surfaces is to be compared (175).…”
Section: Thermal Stimulationmentioning
confidence: 99%
“…Patients with classical trigeminal neuralgia usually have normal or only mildly abnormal trigeminal reflexes, whereas those with symptomatic trigeminal neuralgia typically have reflex abnormalities. 48 A recent study suggested that EP testing may distinguish symptomatic from classical trigeminal neuralgia with a sensitivity of 96% and a specificity of 93%, 49 although more clinical experience is needed. EP testing may also assist lesion localization.…”
Section: Imagingmentioning
confidence: 99%
“…For example, abnormal components of the blink reflex (R1 or R2) may help distinguish a peripheral from central lesion or help localize a lesion within the brainstem. 48 Other potentially useful tests are nerve conduction study of the mental nerve 50 and quantitative sensory testing of patients with sensory symptoms. 22 Sensitivity and specificity of these tests are unknown, as experience in their use is very limited.…”
Section: Imagingmentioning
confidence: 99%
“…The diagnosis of trigeminal nerve damage generally involves the patients' clinical history, questionnaires, clinical examination, and psychophysical testing such as qualitative sensory testing (QualST) and quantitative sensory testing (QST), all of which require subjective responses from the patients [2]. Therefore, more objective investigative options may be valuable adjunct tools in the diagnostic repertoire to assess and confirm for definite neuropathic pain [3][4][5]. One such objective diagnostic test that can be used to attain the level of certainty to designate a diagnosis of definite neuropathic pain is the "nociceptive-specific" blink reflex (nBR) test [4].…”
Section: Introductionmentioning
confidence: 99%